Revision of Eocene Antarctic carpet sharks (Elasmobranchii, Orectolobiformes) from Seymour Island, Antarctic Peninsula - Engelbrecht, Andrea; Mörs, Thomas; Reguero, Marcelo Alfredo; Kriwet, Jürgen (Journal of Systematic Palaeontology)
The highly fossiliferous Eocene deposits of the Antarctic Peninsula are among the most productive sites for fossil remains in the Southern Hemisphere and offer rare insights into high-latitude faunas during the Palaeogene. Chondrichthyans, which are represented by abundant isolated remains, seemingly dominate the marine assemblages. Eocene Antarctic sawsharks have only been known from few isolated rostral spines up to now, that were assigned to Pristiophorus lanceolatus. Here, we present the first oral teeth of a sawshark from the Eocene of Seymour Island and a re-evaluation of previously described Pristiophorus remains from Gondwana consisting exclusively of rostral spines. The holotype of Pristiophorus lanceolatus represents a single, abraded and insufficiently illustrated spine from the Oligocene of New Zealand. All other Cenozoic rostral spines assigned to this species are morphologically very indistinct and closely resemble those of living taxa. Consequently, we regard this species as dubious and introduce a new species, Pristiophorus laevis, based on oral teeth. The combination of dental characteristics of the new species makes it unique compared to all other described species based on oral teeth. Rostral spines from the Eocene of Seymour Island are assigned to this new species whereas those from other Cenozoic Gondwana localities remain ambiguous. Fil: Engelbrecht, Andrea. Universidad de Viena; Austria Fil: Mörs, Thomas. Swedish Museum of Natural History; Suecia Fil: Reguero, Marcelo Alfredo. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. Universidad Nacional de La Plata. Facultad de Ciencias Naturales y Museo. Departamento Científico de Paleontología de Vertebrados; Argentina Fil: Kriwet, Jürgen. Universidad de Viena; Austria